Desafios e perspectivas dos resíduos sólidos no centro de abastecimento de Feira de Santana-BA - Bastos, Carla Alessandra Melo de Freitas (2018)
Solid waste is a significant element in the study of the relationship between society and nature so that anthropogenic actions reveal socio-cultural attitudes, especially the degree of awareness regarding socio-spatial organization and environmental care. In the specific case of Supply Centers, the absence of adequate planning for waste management, as well as financial limitations, has reflected socio-environmental impacts within these establishments. In this context, Geographic Science offers a holistic vision proposal, based on an interdisciplinary and integrative approach to reality, becoming an important tool for understanding these issues. The general objective of the research is to analyze the solid waste management at the Feira de Santana Supply Center, Bahia. The specific objectives are divided into: identifying the positive and negative aspects in the stages of waste management; to ascertain the effectiveness of the legal aspects of municipal solid waste management; analyze the spatial organization of the Supply Center; to characterize the socio-environmental dynamics in waste management. The problem underlying the research is based on the question of how solid wastes are being managed and the hypothesis is based on the principle that the solid waste management practices in the Supply Center have caused socio-environmental impacts. The procedures used to develop the study consist of bibliographic research, survey of secondary data (documentary research) and primary (interviews, application of questionnaires, photographic record), field activities, cartographic elaboration, analysis and integrated discussion of the data. Results confirm, on the one hand, that despite having a waste management system, through the competent agencies, and having advanced the scope of collection / transportation, on the other hand, it lacks monitoring and inspection of the actions and procedures that configure the their local reality. Failure to comply with legal orders is one of the most relevant factors for the Center's current negative scenario. The volume of waste generated is very significant, around 200 to 320 tons / month, in greater quantity of organic origin (80%), considering the activities developed in the area. However, their inadequate management results in problems such as increased waste and shortened life of the landfill, as all the waste collected in the area is directed to it. In this way, there is the urgency of a systematized program of selective collection and Environmental Education, as required by the National Policy on Solid Waste.